Mut̤ālaʻah-yi Ḥāfiẓ aur us se kyā munbasit̤ hotā hai - Ḥaqqī Dihlavī, Muḥammad Iḥtishāmuddīn (SAMP early 20th-century Indian books project ;, 1939)
Critical appreciation of Ḥāfiẓ, 14th cent., Persian poet.